2011
DOI: 10.1188/11.onf.661-668
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an Evidence-Based Order Set to Impact Initial Antibiotic Time Intervals in Adult Febrile Neutropenia

Abstract: The use of an evidence-based approach to nursing care is essential to achieving the best outcomes for patients with febrile neutropenia. Incorporation of current evidence into an order set to guide clinical practice and comprehensive nurse, pharmacy, and physician education are needed for the successful implementation of evidence-based practice changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 27 publications
(58 reference statements)
0
16
0
6
Order By: Relevance
“…The common reasons for delayed in assessment and antibiotic administration reported in literature are: Antibiotics are prescribed by doctors but their administration is delayed, prolonged time to assessment by the junior staff, lack of awareness of natural evolution of course of neutropenic sepsis, failure of the emergency department to stock the appropriate antimicrobial therapy, and lack of a distinct protocol for febrile neutropenia [8,9]. A significant decrease in time-to- antibiotic administration has been demonstrated when order sets were utilized to increase efficiency in antibiotic administration or when multiple ED initiatives were taken to improve patients triage [12-14]. …”
Section: Discussionmentioning
confidence: 99%
“…The common reasons for delayed in assessment and antibiotic administration reported in literature are: Antibiotics are prescribed by doctors but their administration is delayed, prolonged time to assessment by the junior staff, lack of awareness of natural evolution of course of neutropenic sepsis, failure of the emergency department to stock the appropriate antimicrobial therapy, and lack of a distinct protocol for febrile neutropenia [8,9]. A significant decrease in time-to- antibiotic administration has been demonstrated when order sets were utilized to increase efficiency in antibiotic administration or when multiple ED initiatives were taken to improve patients triage [12-14]. …”
Section: Discussionmentioning
confidence: 99%
“…Limitations of the study included a retrospective design and comparison of patients managed in different level hospitals, university and community hospitals, with lack of standardisation for usual care. Best et al () conducted the same design study reviewing 30 FN patients managed without an order set (clinical guideline), comparing them to 23 patients treated with an order set. As with Lim et al’s study, Best et al demonstrated decreased time delays in AB administration when a FN protocol was followed ( t = 2.25; df = 37; p = 0.031).…”
Section: Resultsmentioning
confidence: 99%
“…Patients cared for by clinicians using the guidelines experienced decreased time delays in AB administration (3.9 versus 4.9 hr, p = 0.02). Limitations of the study included a ret rospective design and comparison of patients managed in different level hospitals, university and community hospitals, with lack of standardisation for usual care Best et al (2011). conducted the same design study reviewing 30 FN patients managed without an order set (clinical guideline), comparing them to 23 patients treated with an order set.…”
mentioning
confidence: 99%
“…The importance of prompt reporting of fever should be emphasized for those subjects receiving myelosuppressive chemotherapy. According to Best et al .,[35] initiating antibiotic therapy in a timely manner is important to treat FN because the delay in treatment can increase the patient's risk for sepsis and death. In the study, 27% of the subjects did not know the temperature at which they should seek medical help.…”
Section: Discussionmentioning
confidence: 99%